Effect of B2 morphology on the mechanical properties of B2-strengthened lightweight steels. (May 2019) - Park, Gyeongbae; Nam, C.H.; Zargaran, A.; Kim, Nack J.
Abstract: Tensile properties and formability of B2-strengthened Fe-15Mn-10Al-0.8C-5Ni and Fe-16Mn-8Al-1C-5Ni lightweight steels have been investigated. Our results show that tensile properties along rolling and transverse directions as well as formability are strongly affected by the morphology of B2. The removal of B2 bands and a development of more homogeneous microstructure containing fine B2 particles in Fe-16Mn-8Al-1C-5Ni steel results in isotropic tensile properties and significant improvement of formability compared to B2 bands containing Fe-15Mn-10Al-0.8C-5Ni steel. Moreover, such improvements are achieved without any degradation of tensile properties, despite a much lower fraction of B2 particles in the former than the latter. Graphical abstract: Unlabelled Image